Technical aspects and current clinical applications of the skin and skeletal muscle biopsy in neurological diagnostics: an overview - Dziewulska, Dorota; Kierdaszuk, Biruta; Gogol, Paweł (Folia Neuropathologica, 2022)
This short overview recalls the basic principles and technical aspects of skin and skeletal muscle biopsies in humans with paying special attention to the stages of these procedures essential for further correct morphological diagnosis. Some of these principles may also be useful in animal experimental studies. The authors emphasize the important role of proper thickness of the skin fragment, proper orientation of muscle fibres and a scalpel during skin biopsy, and proper concentration of fixatives. They recommend avoiding anaesthesia of the skeletal muscle itself and using forceps carefully so as not to crush the epidermis.